Innovation And Marketing Capability Impact On Marketing Performance At Semarang Institute Of Technology And Business Campus With Brand Equity And Competitive Advantage As Mediating Variables. - Ersalena, Heni; Soliha, Euis; Kuswardhani, Dc; Sujito, Sujito (Politeknik Negeri Bandung, 2026)
The marketization of higher education has intensified competition among private universities, particularly in emerging economies such as Indonesia. In this context, higher education institutions must strengthen internal capabilities to improve marketing performance. This study examines the effects of marketing capability and innovation capability on marketing performance in Indonesian private higher education institutions, with brand equity and competitive advantage considered as mediating mechanisms. Drawing on the Resource-Based View, a quantitative approach was employed using survey data collected from marketing-related personnel across private universities in Indonesia. The proposed model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that innovation capability significantly enhances brand equity and competitive advantage, while marketing capability positively influences only competitive advantage. Brand equity has a strong positive effect on marketing performance, whereas competitive advantage does not exert a direct effect. Overall, the results suggest that marketing performance in higher education is driven primarily by brand-related assets rather than competitive advantage alone. This study contributes to higher education marketing literature by clarifying how organizational capabilities are translated into market outcomes and offers practical insights for institutional leaders seeking to enhance competitiveness through integrated branding and capability-based strategies.